The Influence of Family Support on the Level of Independence of Older Adults After Stroke in Fulfilling Daily Living Activities in Indonesia: A Literature Review - Mia Haerani; Ummi Malikal Balqis (STIKES Hesti Wira Sriwijaya, 2025)
Introduction: The natural process of aging is accompanied by a decline in physical, psychological, and social conditions that work together to create problems from chronic illnesses, weakness from reduced function of various body organs, and problems with day-to-day activities. Stroke is among the health issues that older adults frequently face. Hemorrhagic and non-hemorrhagic strokes are the two types of strokes. Method: The purpose of this study is to ascertain how much family support affects an older adults' ability to carry out daily activities independently after suffering a stroke. Selected articles from the literature are reviewed and used in this study. Results: Participants discussed two themes regarding the impact of family support: enhancing the quality of life for older adults following a stroke and providing support for older adults to remain independent with their ADLs. Having optimal family support will cause stroke sufferers to become independent in carrying out activities, but if there is no family support, stroke patients will become dependent on other people to fulfill their ADLs. Conclusion: There is no family support, stroke patients will become dependent on other people to fulfill their ADLs.